PEMAHAMAN KONSEP BENTUK ALJABAR DAN KAITANNYA DENGAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS VII MTsN 2 MEDAN - Lailatunnur Kamalia Siregar (State Islamic University of North Sumatra, 2017)
The purpose of this study is to determine: (1) How does an understanding of the concept of operations in the algebra class VII MTsN 2 Field, (2) how mathematics learning outcomes of students in class VII MTsN 2 Field, (3 ) How is the relationship between the understanding of the concept of operations with the algebra mathematics learning outcomes of students in class VII MTsN 2 Field. This research is a quantitative method decryption. The population in this study were student / I class VII MTsN 2 Field. The population in this research were 360 students / class VII I MTsN 2 Field, while the sample in this study taking 20% of the total student population that is 78 people. Instruments of data collection in this research is a test. Based on these results, obtained both variables were normally distributed research. For an understanding of the concept of form algebraic variables (X) obtained x2hitung = -252.11 and students' mathematics learning outcome variable (Y) obtained x2hitung = -13625.02, while x2tabel the significant level α = 5% is equal to 11.070. So for both variables were obtained count x2 > x2 table and this means that the two variables are normally distributed research. In this study correlation coefficient rxy = 0.974, t = 37.48 while. T value table (dk 76: α = 0.05) is equal to 1.995 to obtain t = 37.48> t table = 1.995. While the coefficient determinant of I = 0.94 or 94%, which means the amount of the contribution of independent variables to the dependent variable Y X is 94%, while 6% are determined by other factors. So the conclusions of this research are: there is a relationship between the understanding of the concept of the algebra of the learning outcomes math class VII MTsN 2 Medan.